Elaboration and characterization of cadmium sulfide (CdS) thin films prepared by chemical bath deposition (CBD). (2022) - Smairi, Salma; Hartiti, Bouchaib; Arba, Youssef; Labrim, Hicham; Fadili, Salah; Tahri, Mounia; Belfhailli, Amine; Thévenin, Philippe
Abstract: The chemical bath deposition technique has found great success in recent years as it has become an integral part of the industrial process for the preparation of large-scale solar cells. In this work we have elaborated CdS thin films on glass substrates by the CBD chemical bath deposition technique from an aqueous solution containing CdCl2 and (NH2 )2 CS as sources of sulfide and cadmium ions for different deposition temperatures. The structural, optical and electrical properties measured before and after thermal annealing, showed that the obtained CdS layers crystallize in the hexagonal structure with a preferential orientation (0 0 2) and that the gap value deduced from the transmission measurements is "2.4 eV" with an optical transmission about 80% and resistivity varies between 10 2 and 10 3 Ω.cm depending on the bath temperature.